2005
DOI: 10.1007/s00280-005-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of anthracycline extravasation in mice with dexrazoxane with or without DMSO and hydrocortisone

Abstract: Dexrazoxane has been reported to be protective against anthracycline induced subcutaneous ulceration in mice. It is currently under clinical investigation as an acute antidote in accidental anthracycline extravasation, for which indication topical dimethylsulfoxide (DMSO) and intralesional hydrocortisone are used empirically. We studied the effect in 72 mice of monotherapy with and combined therapy of intraperitoneal dexrazoxane, topical DMSO, and intralesional hydrocortisone as acute antidotes against ulcerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 11 publications
0
88
0
Order By: Relevance
“…Although many of these results appeared interesting, the only additional clinical indication for DEX becomes a protection of tissue in accidental ANT extravasation-a rare, but potentially serious, adverse effect associated with long-lasting local damage, ulceration, and necrosis. Langer et al have reported that systemic treatment with DEX (250 mg/kg or triple treatment with 62.5 mg/kg) markedly decreases the area of wound and healing time when started immediately after induction of ANT extravasation in mice (148,149). However, such effects were not achievable with ADR-925, EDTA, N-acetylcystein, vitamin E, merbarone, or aclarubicin, which does not suggest involvement of iron chelation, oxidative stress, or TOP2 inhibition (149).…”
Section: Dex-afforded Tissue Protection Beyond the Ant-induced Cardiomentioning
confidence: 99%
“…Although many of these results appeared interesting, the only additional clinical indication for DEX becomes a protection of tissue in accidental ANT extravasation-a rare, but potentially serious, adverse effect associated with long-lasting local damage, ulceration, and necrosis. Langer et al have reported that systemic treatment with DEX (250 mg/kg or triple treatment with 62.5 mg/kg) markedly decreases the area of wound and healing time when started immediately after induction of ANT extravasation in mice (148,149). However, such effects were not achievable with ADR-925, EDTA, N-acetylcystein, vitamin E, merbarone, or aclarubicin, which does not suggest involvement of iron chelation, oxidative stress, or TOP2 inhibition (149).…”
Section: Dex-afforded Tissue Protection Beyond the Ant-induced Cardiomentioning
confidence: 99%
“…ICRF-187 can antagonize the effect of these drugs outside the CNS (Hofland et al, 2005b), thereby allowing for a more effective targeting of CNS tumors . Furthermore, ICRF-187 [dexrazoxane (Savene)] has been found to be effective as an antidote against accidental anthracycline extravasation (Langer et al, 2000;Mouridsen et al, 2007). Finally, ICRF-187 (Cardioxane, Zinecard) is also used as a cardioprotectant in anthracycline treatment (Cvetković and Scott, 2005).…”
mentioning
confidence: 99%
“…25 Three animal studies have examined the use of dexrazoxane in mice. [26][27][28] In all 3 studies, injuries caused by subcutaneous anthracycline administration were reduced by intraperitoneal or intravenous dexrazoxane.…”
Section: Literature Reviewmentioning
confidence: 99%